Mitochondrial dysfunction in Alzheimer’s disease: a key frontier for future targeted therapies - Shuguang Wang; Zuning Liao; Qiying Zhang; Xinyuan Han; Changqing Liu; Jin Wang (Frontiers in Immunology)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder, accounting for approximately 70% of dementia cases worldwide. Patients gradually exhibit cognitive decline, such as memory loss, aphasia, and changes in personality and behavior. Research has shown that mitochondrial dysfunction plays a critical role in the onset and progression of AD. Mitochondrial dysfunction primarily leads to increased oxidative stress, imbalances in mitochondrial dynamics, impaired mitophagy, and mitochondrial genome abnormalities. These mitochondrial abnormalities are closely associated with amyloid-beta and tau protein pathology, collectively accelerating the neurodegenerative process. This review summarizes the role of mitochondria in the development of AD, the latest research progress, and explores the potential of mitochondria-targeted therapeutic strategies for AD. Targeting mitochondria-related pathways may significantly improve the quality of life for AD patients in the future.